TINJAUAN KRONOLOGIS TERHADAP KEJAHATAN PERJUDIAN SABUNG AYAM DI KECAMATAN BASSE SANGTEMPE UTARA KABUPATEN LUWU - Salmi, Salmi; Rahman Nur, Abdul; Kamal, Kasmad; Bakar, Abu (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2025)
This research aims to determine the factors that cause cockfighting gambling crimes to occur in the Bastem Police jurisdiction and to determine efforts to overcome cockfighting gambling crimes that occur in North Basse Sangtempe District, Luwu Regency. This research was conducted in North Basse Sangtempe District, Luwu Regency by selecting the agency related to this case, namely in the jurisdiction of the Bastem Police. The data collection methods used were the Interview Method and Documentation Method, then the data obtained was analyzed descriptively qualitatively to reveal the expected results. The results of the research show that the factors that cause the crime of cockfighting gambling are habits or hobbies, environmental or cultural factors, economic factors, as well as weak religious education and law enforcement. Efforts to overcome the crime of cockfighting gambling are taken through preventive measures carried out by the police by providing legal education to the community and increasing supervision, then through repressive efforts by carrying out raids, arrests and conducting investigations.